A USER INTERFACE AND USER EXPERIENCE E-COMMERCE BERBASIS MOBILE - Rani Tarisa; Fatoni Kurniawan; Siti Sauda (JSAI (Journal Scientific and Applied Informatics), 2023)
CV. Global Sakti Mandiri is a place that sells various kinds of electronic devices and also a place that provides electronic services. This study uses the User Centered Design (UCD) method as an approach which is a concept of design through an approach by system users, where the system design process focuses on user needs. The purpose of using this method is to help determine the suitability of the interface of mobile-based e-commerce applications based on attractiveness by users. This prototype is in order to adjust to the wishes and needs of users. Steps of the User Centered Design method. This research will start from the stage of Specify the context of use, then to the second stage of Specify User and organization requirements, then the third stage Produce design solution, and finally Evaluate design. The results of this assessment using the system usability scale (SUS) method showed a score of 73.6 good categories, indicating that the e-commerce system has a good level of user convenience. Users feel that the interface and functionality are easy to use and understand.